JAK/STAT in leukemia: a clinical update - Liang, Dong; Wang, Qiaoli; Zhang, Wenbiao; Tang, Hailin; Song, Cailu; Yan, Zhimin; Liang, Yang; Wang, Hua (Molecular cancer, 2024)
Over the past three decades, considerable efforts have been expended on understanding the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway in leukemia, following the identification of the JAK2V617F mutation in myeloproliferative neoplasms (MPNs). The aim of this review is to summarize the latest progress in our understanding of the involvement of the JAK/STAT signaling pathway in the development of leukemia. We also attempt to provide insights into the current use of JAK/STAT inhibitors in leukemia therapy and explore pertinent clinical trials in this field.